Analisis Respon Siswa Terhadap Pembelajaran Daring Pada Pembelajaran Matematika SD Negeri 29 Sanggau - Siti Nur Asmah; Dessy Setyowati (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This research was aimed to describe the responses of sixth grade students in elementary school number 29 Sanggau about online learning in mathematic class. The method was descriptive qualitative. The instrument for collecting data was questionnaire with yes and no questions consisting four indicators. They were (1) the students’ curiosity in online class, (2) the students’ motivation in online class, (3) the students’ satisfaction in online class, and (4) the students’ interest in online class. The questionnaire was analyzed used Guttman scale. The result showed that the percentage was 58.3% with the category of “low”. It was caused by the factors, they were the limitation of digital platform used during online learning, the bad connection in internet used in the areas, the unvaried application used for teaching learning process, which used whatsapp group. The problems in teaching learning process in the online class hoped can be solved by local education office and the use of varied application in online class.